2016
DOI: 10.2147/ppa.s119719
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of the Morisky Medication Adherence Scale in gout: a prospective study

Abstract: BackgroundThe outcomes of any chronic illness often depend on patients’ adherence with their treatment. A tool is lacking to assess adherence in gout that is standardized, allows real-time feedback, and is easy to understand.ObjectiveWe set out to evaluate the utility of the 8-item Morisky Medication Adherence Scale (MMAS-8) in monitoring medication adherence in a multiethnic Asian gout cohort on urate-lowering therapy (ULT).MethodsThis cohort study recruited patients with gout where baseline and 6-monthly cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…Other significant predictors of non‐adherence among Singaporeans with gout include presence of comorbidities, patient marital status, and education level . Consistent with the published literature on gout, local patients with comorbidities tend to be more adherent .…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…Other significant predictors of non‐adherence among Singaporeans with gout include presence of comorbidities, patient marital status, and education level . Consistent with the published literature on gout, local patients with comorbidities tend to be more adherent .…”
Section: Introductionsupporting
confidence: 68%
“…Only 24% of Singaporean patients on gout medication are highly adherent based on their Morisky Medication Adherence Scale‐8 (MMAS‐8) score, a validated patient self‐report scale that has been found to reliably assess and predict patient medication‐taking behavior . Another local study based on clinical outcome measures (whether patients achieve target SU levels) found that only 25% of patients had controlled SU levels during 1 year of regular care.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations